Hybrid effects of steel fiber and microfiber on the tensile behavior of ultra-high performance concrete. (10th June 2016) - Kang, Su-Tae; Choi, Jeong-Il; Koh, Kyung-Taek; Lee, Kang Seok; Lee, Bang Yeon
Abstract: Ultra-high performance concrete (UHPC) has ultra-high material performance including high strength and high flowability. However, its tensile strain capacity is generally lower than that of high ductile cementitious composite. This study experimentally investigated the effect of hybrid combinations of straight 0.2 mm diameter steel fiber and various microfibers on the mechanical properties of UHPC. Four types of hybrid fiber reinforced UHPCs including steel, basalt fibers, polyvinyl-alcohol, and polyethylene fibers were designed and then compressive strength, density, and tensile behavior were investigated. Test results showed that combining a synthetic fiber with high strength, such as PE fiber, and steel fiber can improve the tensile behavior of UHPC and basalt fiber was effective for improving the tensile strength of UHPC.